An Analysis Of Students’ Writing Skill In Descriptive Text At Grade X1 Ipa 1 Of Man 2 Padang - Lailatul Husna (Jurnal Ilmiah Pendidikan Scholastic, 2017)
This research was a descriptive research with the main aim to analyze the students’ descriptive text quality in English subject. The components that were analized analyzed in the descriptive text written by the students were developing ideas, organizing ideas, grammar, vocabulary and mechanics. These five components were analyzed based on the five categories, they are excellent, good, satisfactory, weak and poor. The participants of this research were 30 students in their second year of MAN 2 Padang. The topic was about places, in which the students chose the place that they want to describe. The technique used to get the participants of the reserach was cluster random sampling technique. The data of the research were taken by using writing test. In this research it was found that the students faced some difficulties in organizing ideas and developing ideas. Some of the students were unable to develop the ideas well. It was also found in their second writing, there were no improvements on the developing ideas. Furthermore, the students were unable to identify and describe the objects in organizing ideas components. In the grammar components, the students did not find major difficulties because the tense was simple present tense which was expressed only in simple sentences. For the vocabulary component, it was found that few students were unable to use the appropriate words to describe the place and they used some Indonesian words too. For the mechanics component, the students did not find major difficulties in using the appropriate mechanics. Based on the result of the research, the students are suggested to pay attention to the whole components of the descriptive text especially in developing and organizing ideas components. It is suggested to the teacher of MAN 2 Padang to use an effective strategy and give various ways to develops students’ ideas. The teacher should help the students to brainstorm the ideas or make an outline of their writing, to help the students to organize and develop their ideas well.